Effect of Key Parameters on Jacalin Extraction from Aqueous Phase into Anionic Reverse Micelles - Sharifah Fathiyah Sy Mohamad; Farhan Mohd Said; Mimi Sakinah Abdul Munaim; Shahril Mohamad (Universitas Gadjah Mada, 2019)
This study demonstrates the extraction of jacalin from crude extract of jackfruit seeds using anionic surfactant based reverse micellar system, sodium bis(2-ethylhexyl) sulfosuccinate (AOT) in isooctane. Effects of various parameters, such as, NaCl concentration (0.05 – 1 M), pH of aqueous phase (pH 4 – 10), AOT concentration (5 – 150 mM), contact time (5 – 30 min) and phase volume ratio (0.5-5) on the transfer efficiency of jacalin was evaluated by changing one factor at a time (OFAT) while keeping the other parameters constant. A maximum of 83% of protein transfer was achieved after equal volume of organic and aqueous phase was stirred for 20 min using 20 mM AOT at pH 5 aqueous phase containing 0.1 M NaCl. The findings demonstrated AOT reverse micellar system as a promising and effective method to extract and purify jacalin from crude protein mixture.